Biocatalytic Friedel–Crafts Acylation and Fries Reaction. (23rd May 2017) - Schmidt, Nina G.; Pavkov‐Keller, Tea; Richter, Nina; Wiltschi, Birgit; Gruber, Karl; Kroutil, Wolfgang
Abstract: The Friedel–Crafts acylation is commonly used for the synthesis of aryl ketones, and a biocatalytic version, which may benefit from the chemo‐ and regioselectivity of enzymes, has not yet been introduced. Described here is a bacterial acyltransferase which can catalyze Friedel–Crafts C‐acylation of phenolic substrates in buffer without the need of CoA‐activated reagents. Conversions reach up to >99 %, and various C‐ or O‐acyl donors, such as DAPG or isopropenyl acetate, are accepted by this enzyme. Furthermore the enzyme enables a Fries rearrangement‐like reaction of resorcinol derivatives. These findings open an avenue for the development of alternative and selective C−C bond formation methods.